Evolution of the american roadster - Riddell, John Dewitt (My University, 1893)
Introduction: Since the pastoral state of the human race, man has understood the hereditary tendency that exists in the perpetuation of a variety, and with this law of nature to assist him the American has founded a breed of horses that represents in no slight degree the nations temperament.
Citation: Riddell, John Dewitt. Evolution of the american roadster. Senior thesis, Kansas State Agricultural College, 1893.
Morse Department of Special Collections
Keywords: America; Horses; Hereditary; Theses; Manuscripts (documents)